Corporate Ownership, Internet Penetration and Internet Financial Reporting: Evidence from the Gulf Cooperation Council Countries - M. Ariff, Akmalia; Bin-Ghanem, Hasan O.; Hashim, Hafiza Aishah (Asian Journal of Business and Accounting, 2018)
Manuscript type: Research paper. Research aims: This study aims to examine how the individual effect of company-level ownership structure and the joint-effect of company-level ownership structure with country-level Internet penetration, can impact on Internet Financial Reporting (IFR). Design/ Methodology/ Approach: An index consisting of 35 IFR items was used to collect information from 152 listed financial com- panies from the Gulf Cooperation Council (GCC) countries. These companies were from Bahrain, Oman, Qatar, Saudi Arabia and the United Arab Emirates. Data were analysed using regression analysis. Research findings: The findings imply that companies with high government and family ownerships have lower extent of IFR. High quality IFR is evident in companies located in countries with a strong Internet penetration. However, the association between corporate ownership structure and IFR is not influenced by the country’s Internet penetration. Theoretical contributions/ Originality: Our study is the first cross- country comparative analysis that utilises data from the GCC coun- tries to explore the determinants of the IFR. This study incorporates company-level governance and country-level institutional factors which are relevant and unique in the context of the GCC to add to the existing evidence that had mainly concentrated on a single-country setting or the developed market. Practitioner/ Policy implications: The findings of this study, which are related to the negative impact of government and family ownership on IFR can be attributed to the regulators in the GCC countries. It is recommended that the GCC improve its enforcement of legal protection for shareholders so as to protect the minority shareholders’ interests. Research limitation: Future cross-country analysis on IFR can focus on other emerging markets that differ from the GCC. In addition, these studies can consider other relevant company-level governance aspects such as managerial ownership and country-level institutional factors such as cyber security risks as variables. Keywords: Ownership, Internet Penetration, Gulf Cooperation Council. JEL Classification: G11, G02, C91